The effect of FDI on job separation - Marc-Andreas Muendler; Sascha O. Becker (Deutsche Bundesbank, 2007)
A novel linked employer-employee data set documents that expanding multinational enterprises retain more domestic jobs than competitors without foreign expansions. In contrast to prior research, a propensity score estimator allows enterprise performance to vary with foreign direct investment (FDI) and shows that the foreign expansion itself is the dominant explanatory factor for reduced worker separation rates. Bounding, concomitant variable tests, and robustness checks rule out competing hypotheses. The finding is consistent with the idea that, given global factor price differences, a prevention of enterprises from outward FDI would lead to more domestic worker separations. FDI raises domestic-worker retention more pronouncedly among highly educated workers and for expansions into distant locations.
Keywords: F21; F23; J63; J23; 330; Multinational enterprises; international investment; demand for labor; worker layoffs; linked employer-employee data; Multinationales Unternehmen; Direktinvestition; Arbeitsplatzsicherung; Beschäftigungseffekt; Schätzung; Industriestaaten